Konstrukcja produktu ubezpieczenia na przykładzie ubezpieczeń zdrowotnych - Osak, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The construction of insurance product (including health insurance) is the effect of product forming process. The product concept selected, construction parameters verbalized in the insurance general terms as well as the form of sale (single product vs. combined product, for example an insurance package) may be used as different levels for analysis of the product construction. The article focuses on the first two mentioned levels of analysis.To treat the product offered by an insurance company exclusively as an insurance protection is only one way of understanding it. A comprehensive understanding of insurance product can be found in the conception presented by M. Haller, which conceives insurance product as a combination of the insurance protection and twofold kind of services - basic services and extended services. The article gives an example of the M. Haller's conception - private health insurance schemes.The overview of the construction of health insurance product from the modifiable parameters point of view has been confined to a presentation of a few chosen specifications regarding the insurance scope (subject, insured, territory, time) combined with insurer's risk limiting instruments. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 73-82